Cardiac and Vascular Surgeons for the Treatment of Aortic Disease: A Successful Partnership for Decision-Making and Management of Complex Cases - Massimo Capoccia MD, MSc (Eng); Soumik Pal MRCS; Michael Murphy FRCS; Maziar Mireskandari FRCS; Andreas Hoschtitzky MSc, FRCSEd (CTh); Christoph A. Nienaber MD, PhD, FESC, FAHA; Nicholas J. Cheshire MD, FRCS; Ulrich P. Rosendahl MD, FETCS (SAGE Publishing, 2021)
Traditionally, cardiac and vascular surgeons have been treating diseases of the aorta as individual specialists. Neither cardiac nor vascular surgeons have ever considered the aorta as a whole, which can be diseased throughout its length at the same time requiring a more thoughtful and different approach. Aortic dissection and aneurysmal disease may well benefit from a multidisciplinary approach. In the context of this review, we discuss examples of joint operating between cardiac and vascular surgeons that may well become a more routine approach in more units in the future.